2021
DOI: 10.1515/opag-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and economic performance of maize (Zea mays L.) as influenced by seed bed configuration and weed control treatments

Abstract: Poor method of weed control and indiscriminate use of herbicides led to low yields, economic returns, and increasing environmental pollution in the southern Guinea savanna of Nigeria. These prompted the conduct of field trials in the 2018 and 2019 cropping seasons to determine the effects of seed bed configuration and weed control treatments on the agronomic and economic performance of maize. The treatments consisted of flat and ridge seed beds and six weed control treatments. The experimental design was a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The adaptability of this weed species made it more competitive with corn crops. It is in line with the findings of Imoloame and Omolaiye (2016) that the types of weeds with the highest relative importance in maize are Paspalum canjugatum and Digitaria horizontalis. The grass weeds were reported to be more competitive and able to suppress the growth of corn plants.…”
Section: Relative Importance Valuesupporting
confidence: 91%
See 1 more Smart Citation
“…The adaptability of this weed species made it more competitive with corn crops. It is in line with the findings of Imoloame and Omolaiye (2016) that the types of weeds with the highest relative importance in maize are Paspalum canjugatum and Digitaria horizontalis. The grass weeds were reported to be more competitive and able to suppress the growth of corn plants.…”
Section: Relative Importance Valuesupporting
confidence: 91%
“…Yield losses due to the presence of weeds ranged from 60-80% caused by uncontrolled weeds in maize (Lagoke et al, 1998). Other studies also agree with Imoloame and Omolaiye (2016), who reported 89% loss of maize yields due to the weeds.…”
Section: Introductionsupporting
confidence: 83%
“…Low soil fertility and the limited use of fertilizers especially nitrogen constitute problems of maize production in sub-Saharan Africa. Also, periodic drought caused by irregular rainfall distribution reduces maize yields by an average of 15% each year (IITA, 2009;Imoloame and Omolaiye, 2016). Oyewole and Ibikunle (2010) observed that weed interference would be a great challenge to maize production, with devastating effects.…”
Section: Introductionmentioning
confidence: 99%
“…[6]. The presence of weeds in a crop is associated with an increase in production costs [7,8]. Weed control in maize is therefore essential and is mainly based on the use of herbicides.…”
Section: Introductionmentioning
confidence: 99%